Vascular endothelial growth factor overexpression does not enhance adipose stromal cell-induced protection on muscle damage in critical limb ischemia - Olea, Fernanda Daniela (2015)
Objectives: Critical limb ischemia complicates peripheral artery disease leading to tissue damage and amputation. We hypothesized that modifying adipose stromal cells (ASCs) to overexpress human vascular endothelial growth factor 165 (VEGF) would limit ischemic muscle damage to a larger extent than nonmodified ASCs. Approach and Results: Rabbits with critical hindlimb ischemia were injected with allogeneic abdominal fat-derived ASCs transfected with plasmid-VEGF165 (ASCs-VEGF; n=10). Additional rabbits received nontransfected ASCs (ASCs; n=10) or vehicle (placebo; n=10). One month later, ASCs-VEGF rabbits exhibited significantly higher density of angiographically visible collaterals and capillaries versus placebo (both P<0.05) but not versus ASCs (both P=NS). Arteriolar density, however, was increased in both ASCs and ASCs-VEGF groups (both P<0.05 versus placebo). ASCs-VEGF and ASCs showed comparable post-treatment improvements in Doppler-assessed peak systolic velocity, blood pressure ratio, and resistance index. Ischemic lesions were found in 40% of the muscle samples in the placebo group, 19% in the ASCs-VEGF group, and 17% in the ASCs groups (both P<0.05 versus placebo, Fisher test). Conclusions: In a rabbit model of critical limb ischemia, intramuscular injection of ASCs genetically modified to overexpress VEGF increase angiographically visible collaterals and capillary density. However, both modified and nonmodified ASCs increase arteriolar density to a similar extent and afford equal protection against ischemia-induced muscle lesions. These results indicate that modifying ASCs to overexpress VEGF does not enhance the protective effect of ASCs, and that arteriolar proliferation plays a pivotal role in limiting the irreversible tissue damage of critical limb ischemia.